A method for manufacturing a biomimetic corneal stromal lens useful for refractive correction

Biomimetic collagen fiber materials prepared by controlled electrochemical assembly and double cross-linking technology, combined with excimer laser engraving, have solved the problems of mechanical properties, precision and biocompatibility of existing refractive error correction materials, achieving high-precision and stable refractive correction effects, and are suitable for minimally invasive surgery.

CN120754321BActive Publication Date: 2025-11-11JIANGSU BOCHUANG BIOTECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511278095.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-11-11
Estimated Expiration
2045-09-09

AI Technical Summary

Technical Problem

Existing refractive error correction materials have shortcomings in terms of mechanical properties, precision control, biocompatibility, and safety, making it difficult to meet the requirements for long-term stable use.

Method used

Biomimetic collagen fiber materials were prepared using controllable electrochemical assembly and double cross-linking technology. Combined with excimer laser engraving, refractive lenses were precisely fabricated. The material has a structure similar to the corneal stroma of the human eye, and possesses high transparency and tissue affinity. The stability and precision of the material were enhanced through photochemical cross-linking and chemical cross-linking.

Benefits of technology

A high-precision, biocompatible refractive correction material has been developed. The material has high stability between corneal layers, avoiding foreign body rejection and tissue damage. The lens refractive power is precisely controllable, making it suitable for minimally invasive surgery and reducing the risk of inflammation and immune response.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120754321B_ABST
    Figure CN120754321B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a bionic corneal stroma lens for refractive correction, and comprises the following steps: solution preparation: type I collagen is dissolved in an acetic acid solution, auxiliary film agent is added, and the solution is fully stirred and centrifuged to remove bubbles to obtain a type I collagen composite solution; lens embryo preparation: the type I collagen composite solution is poured into an assembly tank, titanium metal is set as a working electrode material with a curvature radius of 6.8-8.0 mm, platinum metal is set as a counter electrode material, current parameters are set according to the required thickness of the embryo, the density is 3.50-6.50 mA / cm 2 , after electrochemical assembly and cross-linking curing, a high-transparent corneal embryo material with uniform curvature in all directions and similar fiber structure arrangement to human corneas is formed, and then, precise cutting processing is carried out by means of an excimer laser to obtain a concave / convex stroma lens with a required correction degree, the correction accuracy is high after the corneal layer is implanted, and meanwhile, the bionic corneal stroma lens has excellent performances in terms of in-vivo stability and biological safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, and in particular to a method for preparing a biomimetic corneal stromal lens that can be used for refractive correction. Background Technology

[0002] Refractive error occurs when light cannot form a clear image on the retina after passing through the refractive system without accommodation.

[0003] The simplest way to correct refractive errors is to wear glasses. However, wearing glasses brings great inconvenience to work and daily life. For example, for some people in high-risk industries, if glasses slip off, vision loss can have serious consequences. Contact lenses are popular among some people who care about their appearance, but long-term wear of contact lenses can deform the eye structure and cause protein deposits on the lens surface.

[0004] US company ReVision (patent publication number CN115052554A) designed a corneal inlay, which is prepared using recombinant protein and 2-methacryloyloxyethylphosphocholine (MPC) in a mold. The resulting inlay material is implanted between the corneal layers for the treatment of presbyopia. However, its application has a drawback: the inlay material has poor mechanical properties, only 0.07 MPa, making it difficult to withstand the effects of intraocular pressure on the material over a long period, leading to eventual material failure.

[0005] CN108601861A discloses a collagen gel material, which is prepared by first mixing type I collagen raw material with polyethylene glycol dialdehyde (PEG-DA), and then mixing and cross-linking it with EDCM / NHS in a mold, followed by demolding. It is designed to thicken the corneal interlaminar stroma and alleviate vision loss caused by keratoconus. However, the casting process in a mold results in poor precision control of parameters such as material thickness and curvature, failing to meet the high requirements for material shape precision in refractive surgery. Furthermore, the production process contains chemical cross-linking agents, the residue of which poses a certain risk of foreign body rejection in the sensitive ocular environment, ultimately leading to material degradation and haze of the surrounding corneal tissue.

[0006] Collagen, a crucial natural component of the human corneal stroma, comprises approximately 68% of its composition. The human cornea possesses a unique layered collagen fiber structure. Because the composition and intricate microstructure of artificial corneal materials differ from those of the natural cornea, poor tissue compatibility after implantation is common. Furthermore, material differences lead to variations in nutrient permeability, hydrophilicity, and light transmission, compromising long-term biocompatibility and stability. In addition, refractive lenses require high processing precision; even a 10µm difference in material thickness can result in a ±1.00D visual acuity correction deviation. Due to limitations in mold-making technology, especially with thinner materials, molding methods often cannot meet refractive accuracy requirements. Summary of the Invention

[0007] To address the shortcomings of existing technologies, this invention proposes a method of controlling the electrochemical assembly of collagen to obtain a highly transparent biomimetic collagen fiber material, which is then strengthened through physical / chemical cross-linking to create a biomimetic artificial corneal matrix material. The prepared material has a structure and composition similar to the human corneal matrix, exhibiting higher tissue affinity and avoiding foreign body rejection issues. Its water content and nutrient permeability are consistent with natural tissue, allowing it to remain stably within the corneal tissue long-term without harming surrounding tissues or causing haze. Furthermore, due to its similar physicochemical properties to natural tissue, this material can be precisely processed using excimer laser equipment in hospitals (similar to laser eye surgery), allowing for precise sculpting into concave / convex lenses of different refractive powers to match the patient's required correction. This method offers greater controllability compared to mold-forming methods, stronger batch stability, and a higher product qualification rate. Unlike ICL implantation, which is inserted deeper into the ciliary sulcus, this material is implanted between the corneal layers, resulting in higher long-term stability.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] A method for fabricating a biomimetic corneal stromal lens for refractive correction includes the following steps:

[0010] S1. Solution preparation: Dissolve type I collagen in acetic acid solution, add hydrogen peroxide and film-forming agent, stir thoroughly until homogeneous, centrifuge at 3000~5000 rpm to remove bubbles, and obtain type I collagen complex solution after 10~15 min;

[0011] S2. Preparation of corneal embryo: Type I collagen composite solution is poured into the assembly tank. Titanium is used as the working negative electrode material, and the working negative electrode is set with a radius of curvature of 6.8~8.0mm and connected to the negative terminal of the power supply. Platinum is used as the working positive electrode material, and the working positive electrode is connected to the positive terminal of the power supply. The current and voltage parameters are set according to the required corneal embryo thickness. Under the action of electrochemistry, collagen molecules near the working electrode quickly aggregate and assemble to form collagen fibers and stack to form corneal embryo.

[0012] S3. Control of embryonic body moisture content: Place the corneal embryos obtained in step S2 in an oven at 25℃~37℃ and adjust the moisture content of the embryos to 20%~35%;

[0013] S4. Embryo body temperature control: The corneal embryos whose water content has been regulated in step S3 are pre-cooled for 1-3 hours.

[0014] S5. Photocuring and crosslinking: The corneal embryo obtained in step S4 is subjected to photocuring and crosslinking by placing it under a UV lamp with a wavelength of 254~365nm for 20~150min to obtain an embryo with a cured corneal fiber structure.

[0015] S6. Chemical crosslinking: The corneal embryo obtained in step S5 is placed in a chemical crosslinking agent solution and crosslinked for 2-10 hours to obtain a stable artificial corneal embryo material.

[0016] S7. Washing: Place the stable artificial corneal embryo material obtained in S6 in PBS buffer solution and wash it 5 to 10 times, each time for 20 to 30 minutes.

[0017] S8. Laser engraving: After cleaning in step S7, the corneal embryo is placed on the base mold and engraved by excimer laser to obtain a concave-convex lens with the corrective power.

[0018] Preferably, in step S1, the type I collagen complex solution comprises the following components: 0.1-0.3 wt% collagen, 0.8-2.5 wt% acetic acid, 5-15 wt% hydrogen peroxide, 2-10 wt% film-forming agent, and the remainder purified water.

[0019] Preferably, in step S1, the film-forming agent includes at least one of polyvinylpyrrolidone K30, polyvinylpyrrolidone K90, triethyl glycerol, and polyethylene glycol 400.

[0020] Preferably, in step S2, the side length of the working negative electrode and the working positive electrode is 10~25cm.

[0021] Preferably, in step S2, the working negative electrode and the working positive electrode apply a constant electric field to the type I collagen composite solution, and the current density of the constant electric field is 3.50~6.50 mA / cm². 2 The electrochemical deposition assembly time is 10~40 min.

[0022] Preferably, in step S3, the time spent in the oven is 2-6 hours, and the water content of the embryo is 20%-35%.

[0023] Preferably, in step S4, the temperature of the pre-cooling treatment is 4℃~10℃.

[0024] Preferably, in step S5, the intensity of the ultraviolet lamp is 1200~2500 μw / cm. 2 The vertical distance between the ultraviolet lamp and the corneal stromal embryo is 10~35cm.

[0025] Preferably, in step S6, the chemical crosslinking agent is one or a mixture of glutaraldehyde, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide (EDC / NHS), and 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMTMM), and the concentration of the crosslinking solution is 0.05~0.1 wt%.

[0026] Preferably, in step S8, the excimer laser wavelength is 266~355nm, the pulse energy range is 10~500μJ, and in step S6, the thickness of the etched matrix lens is 10~250μm, the refractive index is 1.33~1.43, and the refractive power is -10D~+10D.

[0027] This invention discloses the preparation of a bionic corneal stromal lens that can be used for refractive correction, which is prepared by the aforementioned method for preparing a bionic corneal stromal lens that can be used for refractive correction.

[0028] The beneficial effects of this invention are:

[0029] 1. When the type I collagen complex solution is assembled by controllable electrochemical process, the current parameters are set according to the required corneal embryo thickness, and the application of electrical signals is precisely controlled, a biomimetic highly transparent material similar to the fiber structure of the human cornea can be obtained. It has significant benefits in nutrient penetration and cell affinity, and has high tissue compatibility.

[0030] 2. The corneal embryo, after being designed with photocuring / chemical double crosslinking, has good mechanical toughness and fiber structure stability, which can meet the long-term stability of the material after implantation into the corneal interlayer and is not affected by deformation or degradation caused by changes in ambient temperature and other factors.

[0031] 3. Unlike femtosecond laser ablation surgery, this invention uses excimer laser processing and sculpting based on corneal topography to match the surface morphology of the material to the patient's corneal topography. The surgical method is truly reversible at both the physical and physiological levels, applicable to additive reversible and minimally invasive surgeries. It eliminates the need to cut the patient's own corneal stroma, preserving intact corneal tissue. Furthermore, the lenticule refractive processing precision is higher, with dimensional accuracy controllable within ±5μm, ensuring more precise refractive correction after implantation.

[0032] 4. The material prepared by this invention has high safety and can be implanted between the corneal stroma layers. There are no blood vessels between the corneal layers, resulting in low immune response and good physiological stability. Implantation will not cause damage to intraocular tissues and the microenvironment. This overcomes the problem that traditional ICL or other lenticule lenses are implanted in the ciliary sulcus filled with aqueous humor. In such cases, the fine particles of the material will detach and participate in the metabolism of the eyeball or other tissues with the aqueous humor, causing inflammation and immune response.

[0033] The features and advantages of the present invention will be described in detail through embodiments and in conjunction with the accompanying drawings. Attached Figure Description

[0034] Figure 1 Illustration of the support mold used in laser engraving;

[0035] Figure 2 This is the state of the lens after cutting in Example 1 under an optical coherence tomography (OCT) scanner;

[0036] Figure 3 This is a comparison chart of the in vitro simulated tear degradation quality of Examples 1-3 and Comparative Example 4;

[0037] Figure 4 These are images showing the state of the lenticule implanted in the stromal layer. (a) is the effect image of the left eye 1 day after lenticule implantation, and (b) is the effect image of the left eye 6 months after lenticule implantation.

[0038] Figure 5 HE section of corneal interlaminar pathology one month after lenticule implantation. Detailed Implementation

[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] Example 1

[0041] S1. Solution preparation: Type I collagen was dissolved in a 0.8% (wt%) acetic acid solution, hydrogen peroxide was 5% (wt%), polyvinylpyrrolidone K30 was 2% (wt%), and the final collagen concentration was 0.1% (wt%), resulting in 1500 mL of type I collagen complex solution; the solution was thoroughly stirred and dispersed, centrifuged at 3000 rpm for 15 min to remove bubbles, and pre-cooled for later use.

[0042] S2. Embryo Preparation: Type I collagen composite solution was poured into the assembly tank. The electrode size was 10×10cm. The titanium electrode was set with a radius of curvature of 6.8mm and connected to the negative terminal of the power supply. Platinum was used as the counter electrode and connected to the positive terminal of the power supply. After energizing, the current density was 3.50mA / cm². 2 The electrodeposition assembly time was 40 minutes. This yielded corneal embryos with uniform curvature in all directions.

[0043] S3. Control of embryonic body moisture content: Place the corneal embryo obtained in step S2 in a 30°C oven for 3 hours to control the moisture content to 30%.

[0044] S4. Embryo temperature control: Transfer the corneal embryos with controlled water content to a 4°C low-temperature chamber for pre-cooling for 2 hours, and then quickly transfer them to the next step.

[0045] S5. Photocuring and crosslinking: The corneal embryo obtained in step S4 is transferred to a 365nm ultraviolet lamp with an intensity of 1200μw / cm². 2 The lamp bead is 10cm vertically from the corneal embryo, and cross-linking is performed for 150min to fix the collagen fiber structure.

[0046] S6. Chemical crosslinking: The corneal embryo obtained in step S5 is placed in a 0.06wt% glutaraldehyde chemical crosslinking agent solution and crosslinked for 2 h to obtain a stable artificial corneal embryo material.

[0047] S7. Washing: The stable artificial corneal embryo material obtained in S6 was placed in 2L PBS buffer solution and washed 8 times, 20 min each time.

[0048] S8. Laser Engraving: The photocured corneal embryo is placed on the base mold, and a 266nm wavelength laser is used with an energy set to 10μJ. The lens cutting size is 56μm. After completion, the sample is placed in a vial containing physiological saline.

[0049] Example 2

[0050] S1. Solution preparation: Type I collagen was dissolved in a 2.5% (wt%) acetic acid solution, with a hydrogen peroxide content of 15% (wt%), a polyvinylpyrrolidone K30 content of 5% (wt%), a polyvinylpyrrolidone K90 content of 5% (wt%), and a final collagen concentration of 0.15% (wt%), yielding 1500 mL of type I collagen complex solution; the solution was thoroughly stirred and dispersed evenly, centrifuged at 4000 rpm for 12 min to remove bubbles, and pre-cooled for later use.

[0051] S2. Embryo Preparation: Type I collagen composite solution was poured into the assembly tank. The electrode size was 25×25cm. The titanium electrode was set with a radius of curvature of 8.0mm and connected to the negative terminal of the power supply. The platinum electrode was used as the counter electrode and connected to the positive terminal of the power supply. After energizing, the current density was 6.50mA / cm². 2 The electrodeposition assembly time was 10 minutes. This resulted in corneal embryos with uniform curvature in all directions.

[0052] S3. Control of embryonic body moisture content: Place the corneal embryonic body obtained in step S2 in a 25°C oven for 2 hours to control the moisture content to 35%.

[0053] S4. Embryo temperature control: Transfer the corneal embryos with controlled water content to a 10°C low-temperature chamber for pre-cooling for 1 hour, and then quickly transfer them to the next step.

[0054] S5. Photocuring and crosslinking: The corneal embryo with a curvature radius of 8.0 mm obtained in step S4 is placed under a 365 nm ultraviolet lamp with an intensity of 2000 μw / cm. 2 The lamp bead is 15cm vertically from the corneal embryo, and cross-linking is performed for 15 minutes to fix the collagen fiber structure.

[0055] S6. Chemical crosslinking: The corneal embryo obtained in step S5 is placed in a 0.05wt% solution of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide (EDC / NHS) chemical crosslinking agent and crosslinked for 10 h to obtain a stable artificial corneal embryo material.

[0056] S7. Washing: Place the stable artificial corneal embryo material obtained in S6 into 2L PBS buffer solution and wash it 5 times, 30 min each time.

[0057] S8. Laser Engraving: The photocured corneal embryo is placed on the base mold, and a 266nm wavelength laser is used with an energy setting of 80μJ. The lens cutting size is 72μm. After completion, the sample is placed in a vial containing physiological saline.

[0058] Example 3

[0059] S1. Solution preparation: Type I collagen was dissolved in a 1.0% (wt%) acetic acid solution, with a hydrogen peroxide content of 10% (wt%), a triethyl glycerol content of 5% (wt%), a polyvinylpyrrolidone K90 content of 3% (wt%), and a polyethylene glycol 400 content of 2% (wt%). The final collagen concentration was 0.3% (wt%), yielding 1500 mL of type I collagen complex solution. The solution was thoroughly stirred and dispersed evenly, centrifuged at 5000 rpm for 10 min to remove bubbles, and pre-cooled for later use.

[0060] S2. Embryo Preparation: Type I collagen composite solution was poured into a deposition tank. The electrode size was 20×20cm. The titanium electrode was set with a radius of curvature of 7.4mm and connected to the negative terminal of the power supply. Platinum was used as the counter electrode and connected to the positive terminal. After energizing, the current density was 4.0mA / cm². 2 The electrodeposition assembly time was 20 minutes. This yielded corneal embryos with uniform curvature in all directions.

[0061] S3. Control of embryonic body moisture content: Place the corneal embryo obtained in step S2 in a 37°C oven for 6 hours to control the moisture content to 20%.

[0062] S4. Embryo temperature control: Transfer the corneal embryos with controlled water content to 7°C and pre-cool them in a low-temperature chamber for 3 hours. After that, quickly transfer them to the next step.

[0063] S5. Photocuring and crosslinking: The corneal embryo with a curvature radius of 7.4 mm obtained in step S4 is rapidly placed under a 254 nm ultraviolet lamp with an intensity of 2500 μw / cm². 2 The lamp bead is 35cm vertically from the corneal embryo, and cross-linking is performed for 20 minutes to fix the collagen fiber structure.

[0064] S6. Chemical crosslinking: The corneal embryo obtained in step S5 is placed in a 0.1wt% solution of 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMTMM) chemical crosslinking agent and crosslinked for 4 h to obtain a stable artificial corneal embryo material.

[0065] S7. Washing: Place the stable artificial corneal embryo material obtained in S6 into 2L PBS buffer solution and wash 10 times, 20 min each time.

[0066] S8. Laser engraving: The photocured corneal embryo is placed on the base mold, and a 355nm wavelength laser is used with an energy setting of 500μJ. The lens cutting size is 108μm. After completion, the sample is placed in a vial containing physiological saline.

[0067] Comparative Example 1

[0068] The only difference between this comparative example and Example 1 is that polyvinylpyrrolidone K30 was not added to the collagen solution.

[0069] Comparative Example 2

[0070] The only difference between this comparative example and Example 1 is that step S3 was not performed, and the corneal embryo was not subjected to moisture control treatment before crosslinking.

[0071] Comparative Example 3

[0072] The only difference between this comparative example and Example 1 is that step S4 was not performed, and the corneal embryo was not subjected to a cooling treatment of 4~10°C.

[0073] Comparative Example 4

[0074] The only difference between this comparative example and Example 2 is that step S6 was not performed, and the corneal embryos were not subjected to further chemical cross-linking treatment.

[0075] The physical properties of the samples from Examples 1-3 and Comparative Examples 1-4 were tested, including transmittance, water content, refractive index, nutrient transmittance, and elastic modulus. Transmittance was measured using a standard transmittance meter at a wavelength of 600 nm. For water content testing, the samples were placed in a 37°C oven until the mass change was less than 0.3 mg, which was recorded as the final mass. Refractive index was measured using an Anton Paar refractometer (Abbemat 550), with the same sample tested three times and the average value recorded. Nutrient transmittance was characterized using a glucose solution permeation test. Elastic modulus was measured using a bio-nanoindenter (Optics 11BV, Piuma) for different matrix lenses; the specific results are shown in Table 1 below.

[0076] Table 1 Sample Test Results

[0077]

[0078] Examples 1-3 are similar to natural human corneas in terms of the aforementioned biological and mechanical properties, demonstrating a high degree of biomimetic performance. However, the experimental solutions or pre-process sample states of Comparative Examples 1-4 were not sufficiently controlled, resulting in significant deviations in the finished product's water content and refractive index from normal corneas. Nutrient transmittance and elastic modulus mechanical properties also decreased to varying degrees, illustrating the significant superior effects of these examples.

[0079] After the samples of Examples 1 to 3 were subjected to different degrees of cutting, the machining accuracy was cross-characterized using the front section OCT and optical thickness gauge. The correction degree and the corresponding theoretical cutting accuracy are shown in Table 2 below.

[0080] Table 2. Different correction degrees and cutting accuracy parameters

[0081]

[0082] Table 2 shows that after precise cutting with excimer laser, the deviation between the theoretical and actual retained thickness of the material is within ±5μm. Compared with soft corneal stroma, the processing accuracy error is small. Furthermore, in Examples 1 to 3 in Table 1, the light transmittance is all above 90%, and the engraving did not damage the light transmittance of the product, which fully demonstrates the toughness and processability of the material.

[0083] Cell viability / cytotoxicity were detected in the samples from Examples 1-3, the negative control, and the positive control. The specific procedure is as follows:

[0084] The matrix lenses were all made to a diameter of 7 mm and soaked in 10 ml of culture medium containing 10% fetal bovine serum. They were then incubated at 37°C for 24 h to prepare the extract. L929 cells cultured in the same manner were diluted, and 100 μL of cell suspension was seeded into each well of a 72-well plate. After 24 h of incubation, the original culture medium was removed, and 100 μL of the extract was added to each well. For the three experimental groups (experimental, negative, and positive control groups), cells were removed 48 h after seeding. 20 μL of 5 g / L MTT solution was added to each well, and the cells were incubated for another 4 h. The liquid in the wells was then removed, and 150 μL of DMSO was added. The plates were shaken for 10 min, and the absorbance was measured at 490 nm using a microplate reader. Cell viability was consistently above 85%, with low cytotoxicity and excellent biocompatibility. (See Table 3 below.)

[0085] Table 3 Cell viability in different groups

[0086]

[0087] The in vitro accelerated degradation experiments of Examples 1-3 and Comparative Example 4 were carried out as follows:

[0088] Enzymatic hydrolysate preparation: Type I collagenase was prepared using Trish-HCl solution to a concentration of 5 U / mL. The matrix lenses processed in Examples 1-3 and Comparative Example 4 were added to an equal volume of the hydrolysate. The hydrolysate was replaced every 12 hours during the test to maintain enzyme activity. The entire hydrolysis process was carried out in a shaker at 37°C. Figure 3 It can be seen that Examples 1-3, having undergone double cross-linking, exhibit more stable performance and are more resistant to degradation in the enzymatic hydrolysate. The total degradation time is approximately 86 hours. In contrast, if only single cross-linking is performed, Comparative Example 4 completely degrades in approximately 28 hours, and its structural morphology cannot maintain its integrity in the later stages, thus failing to perform its intended vision correction function. Comparative Example 4 illustrates the significant advantages of the present invention.

[0089] The biocompatibility experiment of the samples of the present invention was carried out, and the specific process is as follows:

[0090] Six experimental rabbits underwent SMILE surgery in their left eyes using a VisuMax 500 femtosecond laser after deep anesthesia. A stromal lenticule was implanted. A sham surgery was performed in the right eye as a control. The corneal cap thickness was 150 μm, the corneal cap diameter was 7.0 mm, the incision angle was 90°, and the incision length was 2.5 mm. After laser scanning, the negative pressure suction was removed, the corneal incision was dissected, and the corneal stroma was separated. A stromal lenticule with a diameter of 6 mm and a thickness of 100 μm was inserted into the capsular bag using a syringe, flattened, and centered without sutures. The right eye control underwent a sham surgery; after separation of the stroma layers, no lenticule was implanted. All rabbits wore corneal bandage lenses post-operatively. Routine post-operative care included antibiotics and steroid eye drops 3-4 times daily. After one month, the frequency was gradually reduced until discontinued. Post-operative OCT images of the animals' eyes are shown below. Figure 4 Among them, (a) is the effect image of the left eye 1 day after lens implantation, and (b) is the effect image of the left eye 6 months after lens implantation. After long-term experimental comparison, no significant change in material thickness was observed, and the product can continue to function stably within the corneal layers. At 1 month, two rabbits were euthanized, and intact corneas were taken for HE staining and sectioning. Figure 5 No obvious inflammation or infection was observed around the stromal lens, suggesting that it was implanted between the stromal layers. The lens exhibits excellent tissue compatibility and long-term stability.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for fabricating a biomimetic corneal stromal lens for refractive correction, characterized in that: Includes the following steps: S1. Solution preparation: Dissolve type I collagen in acetic acid solution, add hydrogen peroxide and film-forming agent, stir thoroughly until homogeneous, centrifuge at 3000~5000 rpm to remove bubbles, and obtain type I collagen complex solution after 10~15 min; S2. Preparation of corneal embryo: Type I collagen composite solution is poured into the assembly tank. Titanium is used as the working negative electrode material, and the working negative electrode is set with a radius of curvature of 6.8~8.0mm and connected to the negative terminal of the power supply. Platinum is used as the working positive electrode material, and the working positive electrode is connected to the positive terminal of the power supply. The current and voltage parameters are set according to the required corneal embryo thickness. Under the action of electrochemistry, collagen molecules near the working electrode quickly aggregate and assemble to form collagen fibers and stack to form corneal embryo. S3. Controlling embryo moisture content: Place the embryo obtained in step S2 in an oven at 25~37℃ and adjust the embryo moisture content to 20%~35%; S4. Embryo body temperature control: The corneal embryos whose water content has been regulated in step S3 are pre-cooled at a temperature of 4℃~10℃ for 1~3 hours. S5. Photocuring and crosslinking: The corneal embryo obtained in step S4 is subjected to photocuring and crosslinking by placing it under a UV lamp with a wavelength of 254~365nm for 20~150min to obtain an embryo with a cured corneal fiber structure. S6. Chemical cross-linking: The corneal embryo obtained in step S5 is placed in a chemical cross-linking agent solution and cross-linked for 2-10 h to obtain a stable artificial corneal embryo material. S7. Washing: Place the stable artificial corneal embryo material obtained in S6 in PBS buffer solution and wash it 5-10 times, each time for 20-30 minutes. S8. Laser engraving: After cleaning in step S7, the corneal embryo is placed on the base mold and engraved by excimer laser to obtain a concave-convex lens with the corrective power.

2. The method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S1, the type I collagen complex solution comprises the following components: 0.1-0.3 wt% collagen, 0.8-2.5 wt% acetic acid, 5-15 wt% hydrogen peroxide, 2-10 wt% film-forming agent, and the remainder purified water.

3. The method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S1, the film-forming agent includes at least one of polyvinylpyrrolidone K30, polyvinylpyrrolidone K90, triethyl glycerol, and polyethylene glycol 400.

4. The method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S2, the side length of the working negative electrode and the working positive electrode is 10~25cm.

5. The method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S2, the working negative electrode and the working positive electrode apply a constant electric field to the type I collagen composite solution, and the current density of the constant electric field is 3.50~6.50 mA / cm². 2 The electrochemical deposition assembly time is 10~40 min.

6. The method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S3, the time spent in the oven is 2 to 6 hours, and the water content of the embryo is 20% to 35%.

7. The method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S5, the intensity of the ultraviolet lamp is 1200~2500 μw / cm. 2 The vertical distance between the ultraviolet lamp and the corneal stromal embryo is 10~35cm.

8. The method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S6, the chemical crosslinking agent is one or a mixture of glutaraldehyde, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide / N-hydroxysuccinimide (EDC / NHS), and 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMTMM), and the concentration of the crosslinking solution is 0.05~0.1 wt%.

9. A method for preparing a biomimetic corneal stromal lens for refractive correction according to claim 1, characterized in that: In step S8, the excimer laser wavelength is 266~355nm, the pulse energy range is 10~500μJ, the thickness of the etched matrix lens is 10~250μm, the refractive index is 1.33~1.43, and the diopter is -10D~+10D.

10. The fabrication of a biomimetic corneal stromal lens for refractive correction, characterized in that: It is prepared using the method described in any one of claims 1-9 for the fabrication of a biomimetic corneal stromal lens that can be used for refractive correction.

Citation Information

Patent Citations

  • A composite collagen hydrogel material, an implantable ophthalmic device comprising such material and methods of producing the composite collagen hydrogel material and the implantable ophtalmic device

    CN108601861A

  • Visible light curing biological tissue binding material based on natural polymer as well as preparation method and application of visible light curing biological tissue binding material

    CN114392387A

  • Preparation and application of collagen keratoprosthesis with heterogeneous fiber microstructure

    CN119139549A